Profitability Ratio Analysis At PT. Bank Muamalat Indonesia TBK Period 2018-2020 - Maya Novianti; Aulia Khotimatul Prahasani (Penerbit Jurnal Indonesia, 2022)
This study aims to analyze the Profitability Ratios in the form of Return On Assets (ROA), Return On Equity (ROE), Operational Activity Efficiency Ratio (REO) at PT. Bank Muamalat Indonesia, Tbk during the period 2018-2020. This type of research is descriptive quantitative research. Based on the results of the analysis and discussion, the financial performance of PT. Bank Muamalat, Tbk is measured using Return On Assets (ROA), Return On Equity (ROE), Operational Activity Efficiency Ratio (REO), indicating unfavorable financial conditions. This is seen based on the calculation of the average Return On Assets (ROA), Return On Equity (ROE), Operational Activity Efficiency Ratio (REO) during the period 2018-2020 which is predicated four in a poor assessment based on profitability rating criteria in accordance regulations with Bank Indonesia. From the analysis results of this study indicate that PT Bank Muamalat Indonesia, Tbk should be better able to manage capital and increase financing in order to generate profits at the bank and can reduce operating costs owned more effectively and efficiently.